Special Education in Brazil: Legal Aspects - Vernaschi de Oliveira, Lucilia; Raimundo Franci Yaegashi, Solange; Sánchez-Huete, Juan Carlos (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2022)
In Brazil, special education is a school modality that permeates different levels and stages of teaching. It assists students with disabilities, autism spectrum disorder (ASD) and high abilities or giftedness, with the aim of complementing or supplementing academic knowledge. This paper aims to present how special education is organised in our country, based on the main legal provisions and on the characterization of the special education public. Based on qualitative research, we present the organization of Brazilian special education, anchored in international and national documents.